2017
DOI: 10.1002/pip.2865
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting the Ga grading during fast atmospheric processing of Cu(In,Ga)Se2 solar cell absorber layers using elemental selenium vapor

Abstract: We study the sequential fabrication of Cu(In,Ga)Se2 (CIGSe) absorber layers by using an atmospheric pressure selenization with a process duration of only a few minutes and the utilization of elemental selenium vapor from independent Se sources. This technology could proof to be an industrially relevant technology for the fabrication of thin‐film solar cells. Controlling the amount of Se provided during the selenization of metal precursors is shown to be an effective measure to adjust the Ga in‐depth distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 60 publications
(123 reference statements)
2
23
0
Order By: Relevance
“…Combing the results of CGI, GGI, Se, and Na, we can speculate the following scenario: the CIGS sample grown by the three‐stage fabrication procedure inevitably consists of a non‐uniformity in the thickness direction, which not only has a Ga‐grading but also has a Cu deficiency. While such structure is globally beneficial to the device performance, imperfection still occurs. With the co‐deposition of In, Ga, and Se in the third stage of the three‐stage process, the very surface seems to lack of Cu in a high degree.…”
Section: Resultsmentioning
confidence: 99%
“…Combing the results of CGI, GGI, Se, and Na, we can speculate the following scenario: the CIGS sample grown by the three‐stage fabrication procedure inevitably consists of a non‐uniformity in the thickness direction, which not only has a Ga‐grading but also has a Cu deficiency. While such structure is globally beneficial to the device performance, imperfection still occurs. With the co‐deposition of In, Ga, and Se in the third stage of the three‐stage process, the very surface seems to lack of Cu in a high degree.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is essential to control the amount of Se participating in the reaction during selenization heat treatment and maintain a uniform Se activity over a large area, which is essential for high quality CIGSe thin film synthesis. Recently, S.S. Schmidt et al reported a conversion efficiency of 15.5% using an in‐line selenization process that supplies Se vapor through a nozzle array . This result corresponded to the highest efficiency of 2‐step CIGS solar cells produced using Se vapor.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, a range of processes have been assessed. Table presents representative cases where the small area solar cell efficiency is 10% or more . On the other hand, because Se vapor has different characteristics from general gas, several problems can be encountered when it is supplied in the vapor state when attempting to obtain a uniform heat treatment result.…”
Section: Introductionmentioning
confidence: 99%
“…However, a reproducible control of the [Ga]/([In] + [Ga]) throughout the absorber layer prole continues to be a challenge. [13][14][15][16][17][18][19] Finding a straightforward approach to control the [Se]/([S] + [Se]) prole distribution of chalcopyrite absorbers would be an effective alternative route to produce band gap grading congurations.…”
Section: Introductionmentioning
confidence: 99%